Writing Towards Promoting the Empowerment of Persons With Disabilities in Digital Inclusion Texts - Lima, Bernardo Alves Villarinho Lima; Leite, Patricia da Silva Leite; Almeida, Leonelo Dell Anhol Almeida (Teste; 2018: IHC_21, 2018)
Writing technical texts that promote the empowerment of persons with disabilities is an important step towards the social inclusion of persons with diverse needs and conditions. However, few Computer Science events and journals present guidelines for writing about them - even those whose topics of interest involve persons with disabilities - and those that present guidelines often are limited to the adjustment of terminology or digital document accessibility. We review current and emergent practices of writing technical texts about digital accessibility and inclusion of persons who use accessibility resources, and we propose means to direct technical communication towards the promotion of empowerment when writing about persons with disabilities, reviewing not only terminology and document accessibility, but also approaches, and concepts, for user involvement, as well as the creation of narratives that are aware of the users' personal power. We expect this paper to provide directions for technical communicators on writing texts that are more aligned with the fact that each person has power to make a change on their own lives, and that artifacts can be used as means for furthering these choices and enabling persons towards their own objectives.